Alliance and Public Preference for Nuclear Forbearance: Evidence from South Korea. Issue 4 (11th December 2018) - Ko, Jiyoung
Abstract: How does a patron state dampen a client state's domestic aspirations for developing nuclear weapons? What nonproliferation tools most effectively induce a client state's domestic preference for nuclear forbearance? This article assesses the relative effectiveness of three nonproliferation tools available to a nuclear patron: a declaration of extended deterrence, forward deployment of nuclear weapons, and a conditional threat of punishment. More specifically, using experimental data on the South Korean public, this article examines whether nuclear forward-deployment and a conditional threat of punishment are more effective than a declaratory policy in enhancing the credibility of extended deterrence and curbing public aspirations for nuclearization. The experimental results show that neither nuclear forward-deployment nor a conditional threat of punishment reduces public support for nuclear armament significantly more than a declaratory policy. They also reveal that compared to when a nuclear ally does not exist, the three nonproliferation tools do not necessarily dampen the public's preference for developing indigenous nuclear weapons. The robustness of the findings is assessed using an experiment on a small sample of government officials. Taken together, this study provides the first experimental evidence on public perception of different nonproliferation tools in a client state. Video Abstract: